The commercialization of pork products of specific qualities - Martins de Carvalho M.A. (Tradition and innovation in Mediterranean pig production, 2000)
In recent years it has been found that consumers tend to give priority to quality rather than quantity in their choice of foodstuffs, thus creating a desire for specific products of a denominated geographical origin. This market could provide a very important boost to rural development, above all in poorer areas, by way of, on one hand, improvement of the farmers' income and, on the other hand, the stabilization of the rural population in these areas. Protected geographical denominations can constitute an important instrument in the defence of the protected products and for the development of the rural world, by guaranteeing equality of conditions of competition between the producers of the products which benefit from these descriptions. With this paper we propose: (i) to make a brief character description of the 'salpicÆo' and 'chouriça' sausages from Vinhais and (ii) to outline an approach to the commercialization of pork products with specific qualities.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)